2005
DOI: 10.1002/hipo.20102
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral hippocampal volume reduction in adults with post-traumatic stress disorder: A meta-analysis of structural MRI studies

Abstract: Over the last decade a significant number of studies have reported smaller hippocampal volume in individuals with symptoms of post-traumatic stress disorder (PTSD) relative to control groups, and in some cases hemispheric asymmetries in this effect have been noted. However these reported asymmetries have not been in a consistent direction, and other well-controlled studies have failed to observe any hippocampal volume difference. This paper reports a systematic review and meta-analysis of studies in which hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
185
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(213 citation statements)
references
References 75 publications
(173 reference statements)
24
185
1
3
Order By: Relevance
“…This main finding agrees with those from prior animal studies (Fuchs and Flugge, 1998;Kim and Diamond, 2002;McEwen, 1999;Miller and O'Callaghan, 2005) and human clinical MRI studies Geuze et al, 2005;Kitayama et al, 2005;Smith, 2005) indicating that chronic stress is associated with a decreased volume of the hippocampus. To our knowledge, this is the first report of a relationship between a prospectively measured indicator of chronic life stress and hippocampal grey matter volume among otherwise healthy individuals.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This main finding agrees with those from prior animal studies (Fuchs and Flugge, 1998;Kim and Diamond, 2002;McEwen, 1999;Miller and O'Callaghan, 2005) and human clinical MRI studies Geuze et al, 2005;Kitayama et al, 2005;Smith, 2005) indicating that chronic stress is associated with a decreased volume of the hippocampus. To our knowledge, this is the first report of a relationship between a prospectively measured indicator of chronic life stress and hippocampal grey matter volume among otherwise healthy individuals.…”
Section: Discussionsupporting
confidence: 92%
“…Right-lateralized decreases in hippocampal volume are observed in major depressive disorder (O'Brien et al, 2004) and in post-traumatic stress disorder (Bremner et al, 1995), although the mechanisms explaining these unilateral findings are unknown Kitayama et al, 2005;Smith, 2005;Van Petten, 2004). One speculation (Bremner et al, 1995), with some support from the animal literature (Sullivan and Gratton, 2002), is that an asymmetric concentration of stressrelated neurotransmitters, such as serotonin, may partly mediate right-lateralized chronic-stress related changes in the structure and function of the hippocampus and related circuitry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few MRI studies have reported that patients with PTSD have smaller hippocampal volumes, which could be used for the diagnosis of PTSD. 106,107 However, it has been argued that smaller hippocampal volume may reflect a pre-existing vulnerability rather than resulting from the traumatic event. 108 It is believed that PTSD symptoms result from a hypoactive medial prefrontal cortex and a hyperactive amygdala, which is supported by experimental findings in animals and humans.…”
Section: Biomarkers For Differentially Diagnosing Mild Tbi Vs Ptsdmentioning
confidence: 99%
“…Patients suffering from major depression or post-traumatic stress disorder have been reported to exhibit hippocampal volumetric loss (Bremner et al, 2000;Smith, 2005). In animal models, sustained exposure to stress is known to induce dendritic atrophy within the hippocampal CA subfields (Magarinos et al, 1996;Vyas et al, 2002) and to decrease neurogenesis in the dentate gyrus (DG) (Mirescu and Gould, 2006;Pham et al, 2003).…”
Section: Introductionmentioning
confidence: 99%